2007
DOI: 10.1080/14763140701489884
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of biomechanical measures of bowling action legality in cricket

Abstract: Cricket bowling is traditionally thought to be a rigid-arm motion, allowing no elbow straightening during the delivery phase. Conversely, research has shown that a perfectly rigid arm through delivery is practically unattainable, which has led to rule changes over the past years. The current rule requires a bowler not to increase the elbow angle by more than 15 degrees, thus requiring a measurement to confirm legality in "suspect" bowlers. The aims of this study were to evaluate whether the current rule is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…However, Ferdinands and Kersting (2007) found that elbow joint angular displacement could not differentiate between participants who had been previously suspected of "throwing". The authors suggested that using the velocity of elbow extension at ball release would be a conceptually more valid measure in identifying bowlers that use this velocity component of throwing to their advantage.…”
Section: Discussionmentioning
confidence: 91%
“…However, Ferdinands and Kersting (2007) found that elbow joint angular displacement could not differentiate between participants who had been previously suspected of "throwing". The authors suggested that using the velocity of elbow extension at ball release would be a conceptually more valid measure in identifying bowlers that use this velocity component of throwing to their advantage.…”
Section: Discussionmentioning
confidence: 91%
“…While research examining the area of illegal actions in cricket has been undertaken, the primary focus has involved quantifying or exploring improved methods for the accurate measurement of elbow kinematics . While this research has explored important issues, the underlying and fundamental question, what is the relationship between elbow extension values and known performance benefits, has yet to be sufficiently answered.…”
Section: Introductionmentioning
confidence: 99%
“…It will also provide support staff with knowledge that will allow better coaching of bowlers, while also facilitating remediation of bowlers with illegal actions. To date, research attempting to explore the performance benefits of bowling with an illegal action has been limited to small bowling cohorts, in‐silico modeling of the effect of elbow fixed flexion, or simple planar analysis of fast bowling …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 To add on, another research study compared twodimensional (2D) video analysis with 3D motion analysis to assess fast bowling action of Indian male university level fast bowlers. 30 The concept of biomechanical analysis is still quite new to Indian cricket compared to other cricketing nations where there have been numerous research studies conducted over the past decade, such as Dr Rene Ferdinands' investigations which include the use of 3D motion analysis system to assess lumbar segment kine matics of fast bowlers, 31 evaluating biomechanical measures of fast bowling to differentiate between legal and suspect bowling actions 32 and more recently, examining the dynamics of spin bowling using a smart cricket ball and a cortex motion analysis system. 33 Research on biomechanical aspects of the game of cricket in India is relatively new.…”
Section: Sports Medicine and Indian Cricketmentioning
confidence: 99%